2016
DOI: 10.35188/unu-wider/2016/151-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in child investment behaviour among agricultural households: Evidence from the Lesotho Child Grants Programme

Abstract: This study has been prepared within the UNU-WIDER project on 'The political economy of social protection systems' which is part of a larger research project on 'The economics and politics of taxation and social protection'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…We consider whether the child is currently enrolled in any educational grade, distinguishing between boys and girls education. 8 The results are striking and are consistent with Sebastian et al (2016). 9 CGP positively and significantly affect school enrolment of boys but not of girls, especially in female headed households.…”
Section: Difference In Difference Approachsupporting
confidence: 52%
See 1 more Smart Citation
“…We consider whether the child is currently enrolled in any educational grade, distinguishing between boys and girls education. 8 The results are striking and are consistent with Sebastian et al (2016). 9 CGP positively and significantly affect school enrolment of boys but not of girls, especially in female headed households.…”
Section: Difference In Difference Approachsupporting
confidence: 52%
“…The results are not reported here but are available upon request. 9 Using the same data but adopting a different analytical framework, Sebastian et al (2016) specifically look at impact of CGP on children schooling, labour and time use, with a particular focus on differentiated impacts by gender and household structure. Note: Robust t-statistics clustered at the community level are in brackets.…”
Section: Difference In Difference Approachmentioning
confidence: 99%
“…Several quantitative studies document the effects of unconditional cash transfer programs, such as Malawi’s SCTP, on child and adolescent work (see also De Hoop & Rosati, 2014). 3 Most of these studies find that such programs lower participation in economic activities and household chores (Covarrubias, Davis, & Winters, 2012; Edmonds, 2006; Edmonds & Schady, 2012; Handa et al, 2016; Sebastian et al, 2016). The quantitative evaluation of Malawi’s SCTP program referred to in the introduction (De Hoop et al, 2017) finds the opposite pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The reason female recipients may be more likely to spend the money in farm activities could be related to women facing higher barriers in participating in the paid labour market. In fact, previous research has found that a greater engagement in farm labour of adult women in female‐headed households (Sebastian et al ., ). One further reason may be related to other characteristics of the programme, such as targeting.…”
Section: Resultsmentioning
confidence: 97%